Digital Diplomacy in Crisis: Indonesia's COVID-19 Pandemic Response - Akbar, Dhanang Fawaiz (Global and Policy Journal of International Relations, 2024)
ABSTRACT The COVID-19 pandemic has fundamentally altered global diplomacy, requiring states to embrace digital media as their main instrument for international participation. This paper investigates the impact of digital diplomacy on Indonesia's handling of the Covid-19 problem. It emphasizes how the country utilized online platforms to handle international relations, distribute vital public health information, and facilitate cooperation across borders. The paper examines the effectiveness of Indonesia's digital diplomacy in addressing the problems presented by the epidemic through examining social media initiatives and international collaborations. The findings demonstrate that digital diplomacy enabled immediate information interchange and enhanced Indonesia's worldwide influence. However, it also revealed weaknesses in digital infrastructure and communication methods. This study enhances the comprehension of digital diplomacy as a crucial element of disaster response, providing valuable insights into its capabilities and constraints in addressing worldwide health emergencies. Keywords: Digital diplomacy, Disaster Response, Covid-19, Collaboration ABSTRAK Pandemi COVID-19 telah mengubah diplomasi global secara mendasar, yang mengharuskan negara-negara untuk menggunakan media digital sebagai instrumen utama mereka untuk partisipasi internasional. Artikel ini menyelidiki dampak diplomasi digital terhadap penanganan masalah Covid-19 di Indonesia. Artikel ini menekankan bagaimana negara tersebut memanfaatkan platform daring untuk menangani hubungan internasional, mendistribusikan informasi kesehatan kepada masyarakat, dan memfasilitasi kerja sama lintas batas. Artikel ini mengkaji efektivitas diplomasi digital Indonesia dalam mengatasi masalah yang ditimbulkan oleh epidemi tersebut melalui pemeriksaan inisiatif media sosial dan kolaborasi internasional. Temuan penelitian menunjukkan bahwa diplomasi digital memungkinkan pertukaran informasi langsung dan meningkatkan pengaruh Indonesia di seluruh dunia. Namun, hal itu juga mengungkapkan kelemahan dalam infrastruktur digital dan metode komunikasi. Studi ini meningkatkan pemahaman diplomasi digital sebagai elemen penting dari respons bencana, memberikan wawasan tentang kemampuan dan kendalanya dalam menangani keadaan darurat kesehatan di seluruh dunia. Kata Kunci: Diplomasi Digital, Respon Bencana, Covid-19, Kolaborasi